2021
DOI: 10.1097/corr.0000000000002065
|View full text |Cite
|
Sign up to set email alerts
|

Improved Clinical Outcomes After Lateralized Reverse Shoulder Arthroplasty: A Systematic Review

Abstract: Background Lateralized reverse shoulder arthroplasty (RSA) has emerged as an attempt to improve on some of the drawbacks of conventional RSA, such as glenoid notching and decrease in ROM. Although this new design is being used in clinical practice, the evidence is mostly limited to case series and has not been systematically reviewed. Questions/purposes (1) How much did patient-reported outcome measures (PROMs) and ROM improve among patients who receive a lateralized RSA implant? (2) What proportion of shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Cuff et al [3], in their clinical series, found only 9% of shoulders demonstrated notching, and they observed 90% survivorship at 10-year follow-up with one lateralized design. In the current study, Nunes et al [8] help us understand that baseplate loosening, or pull-out, is not a concern, and at mid-term follow-up, lateral offset RTSA is a viable option. But we have yet to determine whether lateralized implants perform better than those with a medial center of rotation.…”
Section: Where Do We Need To Go?mentioning
confidence: 87%
See 2 more Smart Citations
“…Cuff et al [3], in their clinical series, found only 9% of shoulders demonstrated notching, and they observed 90% survivorship at 10-year follow-up with one lateralized design. In the current study, Nunes et al [8] help us understand that baseplate loosening, or pull-out, is not a concern, and at mid-term follow-up, lateral offset RTSA is a viable option. But we have yet to determine whether lateralized implants perform better than those with a medial center of rotation.…”
Section: Where Do We Need To Go?mentioning
confidence: 87%
“…W. J. Warme ✉, University of Washington, Department of Orthopaedic Surgery, Seattle, WA98195-6500, USA, Email: warmewj@u. washington.edu with one lateralized design. In the current study, Nunes et al [8] help us understand that baseplate loosening, or pull-out, is not a concern, and at midterm follow-up, lateral offset RTSA is a viable option. But we have yet to determine whether lateralized implants perform better than those with a medial center of rotation.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Technetium-99 m three-phase bone scan imaging is sensitive for arthroplasty failure but is limited in determining the etiology [37,45].…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…The RTSA reverses the normal anatomy of the shoulder joint, replacing the glenoid component with a ball and replacing the humeral head with a socket. The reverse anatomy repositions the center of rotation and utilizes distalization of the humerus, thus restoring the tension of the deltoid muscle, which becomes the primary muscular force to move the shoulder [4,45]. The RTSA is a semi-constrained design which provides a stable fulcrum, as well as static stability and increased range of motion [45,60].…”
Section: Reverse Arthroplasty Reverse Total Shoulder Arthroplasty (Rtsa)mentioning
confidence: 99%